Carbon Loss Pathways in Degraded Peatlands: New Insights From Radiocarbon Measurements of Peatland Waters. Issue 7 (13th July 2022) - Evans, Martin G.; Alderson, Danielle M.; Evans, Chris D.; Stimson, Andrew; Allott, Timothy E. H.; Goulsbra, Claire; Worrall, Fred; Crouch, Tia; Walker, Jonathan; Garnett, Mark H.; Rowson, James
Abstract: Peatland carbon stores are under widespread anthropogenic pressure, resulting in degradation and carbon loss. This paper presents DO 14 C (Dissolved Organic Carbon) dates from waters draining two eroded blanket peatland catchments in the UK. Both catchments are characterized by severe gully erosion but one additionally has extensive surface erosion on unvegetated surfaces. DO 14 C values ranged from 104.3 to 88.6 percent modern (present to 976 Before Present). The oldest DOC dates came from the catchment characterized by both gully and surface erosion and are among the oldest reported from waters draining temperate peatlands. Together with peat age‐depth data from across the peatland landscape, the DO 14 C ages identify where in the peat profile carbon loss is occurring. Source depths were compared with modeled water table data indicating that in the catchment where gully erosion alone dominated, mean water table was a key control on depth of DOC production. In the system exhibiting both gully erosion and surface erosion, DOC ages were younger than expected from the age of surficial peats and measured water tables. This may indicate either that the old organic matter exposed at the surface by erosion is less labile or that there are modifications of hydrological flow pathways. Our data indicate that eroded peatlands are losing carbon from depth, and that erosion form may be a control on carbon loss. Our approach uses point measurements of DO 14 C to indicate DOC source depths and has the potential to act as an indicator of peatland function in degraded and restored systems. Plain Language Summary: Peatlands are the largest terrestrial soil carbon store, but are under widespread anthropogenic pressure, resulting in degradation and carbon loss. In this study of UK upland peatlands, we used radiocarbon dating of dissolved organic carbon (DOC) from waters draining eroded peatlands to identify the age of the carbon that has been lost. These dates are among the oldest reported from waters draining temperate peatlands. The dates combined with age‐depth data from across the peatland landscape allowed us to model where in the peat profile the carbon loss was concentrated. We compared these results with water table data and found that in the systems we studied, the type of peatland erosion that the system had experienced was an important factor controlling the age of carbon lost. The close association between radiocarbon age of carbon and water table suggested that radiocarbon dating of DOC might be a useful catchment scale proxy for water table, a direct measurement of the locus of carbon loss from the peat, and an effective measure of the overall "health" of the peatland ecosystem. The approach therefore has potential as a rapid method of assessing stabilization and restoration of intact peatland function. Key Points: We present old 14 C dates from waters draining eroded temperate peats, caused by deep C loss and low water tables in gullied peats Novel approaches to dissolved organic carbon source identification indicate that water table drawdown and the nature of peat erosion influence loss of old carbon Our method has potential as a rapid way to indicate peatland function and assess restoration success